Trichophyton erinacei onychomycosis: The first to evidence a proximal subungual onychomycosis pattern - Sutasinee Phaitoonwattanakij (2020)
© 2019 The Author(s). Published by S. Karger AG, Basel. Trichophyton erinacei is an emerging cause of dermatophyte infections, which are frequently isolated from hedgehogs. Nail infections from T. erinacei are rarely reported. We describe the case of a 23-year-old Thai female who had a history of systemic lupus erythematosus with lupus nephritis type III and who developed widespread skin and nail infections caused by T. erinacei that were most likely transmitted from a hedgehog. Although the patient did not demonstrate a clinical improvement or mycological cure following systemic itraconazole and fluconazole treatment, she achieved clinical and mycological cures after terbinafine therapy. A drug susceptibility test should be performed in patients with T. erinacei infections to facilitate decision-making about antifungal therapy. Here, we are the first to report a case of proximal subungual onychomycosis from a T. erinacei infection.